O medo social e o cotidiano: um estudo de como o jornal já aborda o medo em suas narrativas e quais as suas relações com o grotesco - Franco, Luís Carlos Venceslau (2017)
This research had as its main focus the study of the narratives of the newspaper Já in relation to an externality marked by the growing Culture of Fear in the whole of society, in our case more specifically in the context of João Pessoa and Paraíba. This culture, which places entire populations in a state of precaution and permanent mistrust, has changed behaviors, changed sociabilities and the way the city sees itself. But regardless of the degree of influence of this culture on the media, and the media on the audience, we will limit ourselves to observing how the narratives of a newspaper, which deals closely with the pattern of violence, relate to components that concern social fear increasingly linked to the impact of crime. The attention to the narratives constitutes one of the stages of the research, which dealt with three events reported by Já between May and October of 2015. The first one, and the one that had the greatest repercussion, was known as "Barbárie dos Bancários", a crime that resulted in a kidnapping of two women and a baby and later in the death of one of the women. The other case concerns the murder of a boy in the town of Sumé, in the interior of the state, in a ritual of "black magic" that had the participation of his own mother. The third case, reported on two occasions, concerns a bus burning and chaos set up by bandits in the city of Campina Grande, whose leadership and idealization of the actions came from leaders of factions imprisoned in the city's prisons. For the analysis of all the cases, we will take into account approaches regarding deviation, the spectacular treatment and the emphasis of the grotesque character. The other stage of the survey, which involved a quantitative approach (from the survey to the quantification of data), focused on the scheduling frequencies of the occurrences, the types of crimes most recorded, the most cited cities, the days, weeks and months with the highest placements The number and type of occurrences per neighborhood and zone. We have used a tool, the SPSS computer program, which allows the decoding of each unit of analysis (news) in several variables and, at a later time, allows the creation of graphs and tables where the data can be crossed. Thus, we could, in a more detailed way, arrive at a cartography of the newspaper, in what concerns to news of violence, and thus to observe their tendencies of scheduling in that period.